A critical analysis of 57 cases of Hughes-Stovin syndrome (HSS). A report by the HSS International Study Group (HSSISG). (15th May 2021) - Emad, Yasser; Ragab, Yasser; Kechida, Melek; Guffroy, Aurelien; Kindermann, Michael; Robinson, Cal; Erkan, Doruk; Frikha, Faten; Ibrahim, Ossama; Al-Jahdali, Hamdan; Silva, Rafael S.; Tornes, Leticia; et al.
Abstract: Background: Hughes-Stovin syndrome (HSS) is a systemic disease characterized by widespread vascular thrombosis and pulmonary vasculitis with serious morbidity and mortality. The HSS International Study Group is a multidisciplinary taskforce aiming to study HSS, in order to generate consensus recommendations regarding diagnosis and treatment. Methods: We included 57 published cases of HSS (43 males) and collected data regarding: clinical presentation, associated complications, hemoptysis severity, laboratory and computed tomography pulmonary angiography (CTPA) findings, treatment modalities and cause of death. Results: At initial presentation, DVT was observed in 29(33.3 %), thrombophlebitis in 3(5.3%), hemoptysis in 24(42.1%), and diplopia and seizures in 1 patient each. During the course of disease, DVT occurred in 48(84.2%) patients, and superficial thrombophlebitis was observed in 29(50.9%). Hemoptysis occurred in 53(93.0%) patients and was fatal in 12(21.1%). Pulmonary artery (PA) aneurysms (PAAs) were bilateral in 53(93%) patients. PAA were located within the main PA in 11(19.3%), lobar in 50(87.7%), interlobar in 13(22.8%) and segmental in 42(73.7%). Fatal outcomes were more common in patients with inferior vena cava thrombosis ( p = 0.039) and ruptured PAAs ( p < 0.001). Death was less common in patients treated with corticosteroids ( p < 0.001), cyclophosphamide ( p < 0.008), azathioprine ( p < 0.008), combined immune modulators ( p < 0.001). No patients had uveitis; 6(10.5%) had genital ulcers and 11(19.3%) had oral ulcers. Conclusions: HSS may lead to serious morbidity and mortality if left untreated. PAAs, adherent in-situ thrombosis and aneurysmal wall enhancement are characteristic CTPA signs of HSS pulmonary vasculitis. Combined immune modulators contribute to favorable outcomes. Highlights: Hughes-Stovin syndrome (HSS) is characterized by widespread vascular thrombosis with serious morbidity and mortality if left untreated. Our report is the first attempt to collect a large cohort of HSS patients to critically analyze the diverse clinical presentations of the disease and important associations that can lead to fatal outcome. Careful interpretation of the radiological images by CTPA is necessary. Notably PAAs can affect all PA branches in association with adherent in-situ thrombosis, and aneurysmal wall enhancement signifies an underlying vasculitic process, which are important radiological signs if the diagnosis of HSS is considered.